Studies on the host-pathogen interactions for Rhizoctonia solani AG2-1 causing damping-off disease of Brassica napus (Oilseed Rape) - Sims, Isabelle Louise (2023)
Rhizoctonia solani is a necrotrophic soil-borne plant pathogen species complex, of which anastomosis group (AG) 2-1 causes devastating disease on oilseed rape (OSR, Brassica napus). It is frequently isolated from arable crop fields where it affects establishment and yield via pre- and post-emergence damping off, hypocotyl and root rot. Genetic resistance to R. solani AG2-1 has not been observed and long-lived sclerotia, plus a broad host range allow the pathogen to survive in the soil for many years. Here, the interactions between Rhizoctonia solani AG2-1, its crop host OSR and the model organism Arabidopsis thaliana were explored. Variation in responses to R. solani were observed between commercial OSR varieties and gene expression data showed that susceptibility was associated with auxin and abscisic acid signalling, and the MYC2 branch of jasmonate signalling, while reactive oxygen species, ethylene signalling and the ERF/PDF branch of jasmonate signalling were associated with increased tolerance. This was supported by inoculation of A. thaliana defence mutants and microscopy using Jas9:VENUS and IAA2pro:GUS lines. Further investigations into the role of auxins in R. solani AG2-1 – A. thaliana interactions showed that R. solani was able to differentially affect the root architecture of WT and aux1 transport mutants. Experiments showing the effects of 2,4-D, PAA and NAA demonstrated that PAA was able to restore gravitropism in aux1. R. solani produced both IAA and PAA when grown in broth culture and growth stimulation was observed when R. solani was grown in broth with low concentrations of exogenous PAA. Analysis of gene expression markers (GEMS) from a previous genome wide association study (GWAS) provided further evidence for the involvement of auxins, jasmonates and ethylene in the defence responses of OSR to R. solani AG2-1. Corresponding A. thaliana candidate gene mutants were inoculated with R. solani AG2-1 under experimental conditions to identify potential susceptibility genes. Two of these were taken further and B. rapa TILLING line resources were developed. This thesis increases understanding of the defence pathways involved in resistance and susceptibility to R. solani AG2-1, examines the influence that R. solani has on the root architecture of auxin mutants, and provides candidate gene TILLING line resources for future work.